Estimating Listeria monocytogenes growth in ready-to-eat chicken salad using a challenge test for quantitative microbial risk assessment - Bernardo, Rita (2022)
Research Areas: Public, Environmental & Occupational Health ; Mathematics ; Mathematical Methods In Social Sciences